Structured Reporting of Head and Neck Sonography Achieves Substantial Interrater Reliability - Ernst, Benjamin Philipp; Dörsching, Carla; Bozzato, Alessandro; Gabrielpillai, Jennis; Becker, Sven; Froelich, Matthias Frank; Kramer, Benedikt; Sproll, Christoph; Schapher, Mirco; Goncalves, Miguel; Mansour, Naglaa; Hofauer, Benedikt; Sommer, Wieland H; von Scotti, Felix; Weimer, Johannes Matthias; Künzel, Julian (Ultrasound International Open, 2023)
Purpose Ultrasound examinations are often criticized for having higher examiner dependency compared to other imaging techniques. Compared to free-text reporting, structured reporting (SR) of head and neck sonography (HNS) achieves superior time efficiency as well as report quality. However, there are no findings concerning the influence of SR on the interrater reliability (IRR) of HNS.Materials and Methods Typical pathologies (n=4) in HNS were documented by video/images by two certified head and neck ultrasound instructors. Consequently, structured reports of these videos/images were created by n=9 senior physicians at departments of otolaryngology or maxillofacial surgery with DEGUM instructors on staff. Reports (n=36) were evaluated regarding overall completeness and IRR. Additionally, user satisfaction was assessed by a visual analog scale (VAS).Results SR yielded very high report completeness (91.8%) in all four cases with a substantial IRR (Fleiss‘ κ 0.73). Interrater agreement was high at 87.2% with very good user satisfaction (VAS 8.6).Conclusion SR has the potential to ensure high-quality examination reports with substantial comparability and very high user satisfaction. Furthermore, big data collection and analysis are facilitated by SR. Therefore, process quality, workflow, and scientific output are potentially enhanced by SR.
Keywords: ultrasonography; structured reporting; quality improvement; interrater reliability